The Lowery collection : a descriptive list of maps of the spanish possessions within the presente limits of the United States, 1502-1820 / by Woodbury Lowery ; edited with notes by Philip Lee Phillips - Phillips, Philip Lee; Lowery, Woodbury
En el lomo: Library of Congress